A structurally-consistent CASH+ sublattice solid solution model for fully hydrated C-S-H phases: Thermodynamic basis, methods, and Ca-Si-H2O core sub-model. (January 2022) - Kulik, Dmitrii A.; Miron, George Dan; Lothenbach, Barbara
Abstract: A new thermodynamic model, CASH+, is proposed, aimed at accurately describing equilibrium composition, stability, solubility, and density of C-S-H gel-like phases at varying chemical conditions. Taking advantage from recent atomistic and spectroscopic studies, this sublattice solid solution model allows incremental extensions to accommodate alkali, aluminum and other cations. This incrementality, achieved first time for a C-S-H solid solution model, means that all thermodynamic properties of endmembers and interaction parameters can be kept fixed in further extensions. This paper describes principles of how endmembers of CASH+ solid solution model can be constructed by permutating moieties assigned to different sublattices, and how the structural consistency of the model can be established. Initial standard thermodynamic properties of endmembers were estimated using predictive methods and PSI/Nagra and Cemdata18 chemical thermodynamic databases. The parameterized core CASH+ sub-model in Ca-Si-H2 O system is shown to perform well in presence of liquid water at temperatures up to 90 °C. Graphical abstract: Highlights: A new CASH+ core thermodynamic model (Ca-Si-H2 O sub-system) is presented. It is a non-ideal sublattice solid solution model based on defect tobermorite structure. It can be accurately fitted to most experimental data, including mean chain length. It computes C-S-H solubility at temperatures 10 to 90 °C in presence of liquid water. This incrementally expandable model opens up new perspectives in cement chemistry.